Conflict Management Between the School and the Guarantee of Students in Social Media in Islamic Education - Rayhan Ali Arifin (IAIN Batusangkar, 2021)
In the all-digital era and the era of information and communication openness coupled with the pandemic period, causing various and varied conflicts in various fields of life. conflict is motivated by various things, and managers must immediately resolve the existing conflict, and it will have a negative impact if it is not handled properly. In the world of education, conflicts between schools and parents often occur, especially in the digital era and the use of social media in interacting indirectly which often creates assumptions and prejudices that lead to conflict. In this article, the author examines the causes of conflict between the school and the guardians of students on social media and their management using a descriptive qualitative approach. The research subjects were several school managers, institutional coaches and guardians of students. The results of the study show that many conflicts occur in social media due to misunderstandings, egos and prejudices that are put forward. The solution is in the form of a spiritual, personal, cross-check and deliberation approach.